2021
DOI: 10.1108/ribs-07-2020-0075
|View full text |Cite
|
Sign up to set email alerts
|

Animosity leads to boycott and subsequent reluctance to buy: evidence from Sino Indian disputes

Abstract: Purpose The purpose of this paper is to investigate if animosity outbreaks against China result in a consumer’s reluctance to buy Chinese goods. It further studies the relationship of consumer animosity upon boycott and reluctance to buy (RTB). Design/methodology/approach A descriptive research design was applied by using the self-administered survey method for collecting data from 473 participants, mostly working graduates from the metropolitan city of Delhi in India. Thereafter, the measurement model was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…This type of animosity was originally evaluated by Klein et al (1998) with their Klein-Ettenson-Morris (KEM) animosity model of foreign product purchase. Numerous studies have confirmed the impact of consumer animosity on product attitudes and purchase intentions in different national settings, such as American consumers' attitudes toward Chinese (Witkowski, 2000) and Russian goods (Harmeling et al, 2015); Chinese (Antonetti et al, 2019;Harmeling et al, 2015;Klein et al, 1998;Yang et al, 2015), Korean (Lee and Chon, 2021) and American (Klein, 2002) attitudes and their boycotts toward Japanese products and Indian consumers' animosity and purchase intentions toward Chinese products (Raman and Aashish, 2021;Sengupta, 2022;Verma, 2021).…”
Section: Theoretical Background 21 Consumer Animositymentioning
confidence: 98%
“…This type of animosity was originally evaluated by Klein et al (1998) with their Klein-Ettenson-Morris (KEM) animosity model of foreign product purchase. Numerous studies have confirmed the impact of consumer animosity on product attitudes and purchase intentions in different national settings, such as American consumers' attitudes toward Chinese (Witkowski, 2000) and Russian goods (Harmeling et al, 2015); Chinese (Antonetti et al, 2019;Harmeling et al, 2015;Klein et al, 1998;Yang et al, 2015), Korean (Lee and Chon, 2021) and American (Klein, 2002) attitudes and their boycotts toward Japanese products and Indian consumers' animosity and purchase intentions toward Chinese products (Raman and Aashish, 2021;Sengupta, 2022;Verma, 2021).…”
Section: Theoretical Background 21 Consumer Animositymentioning
confidence: 98%
“…Thus, these boycotts could be on a nationwide level (Luo & Zhou, 2020). An individual or group may engage in a boycott if they feel social pressure to do so, according to one school of thought (Verma, 2022). When it comes to politics in general, Ali and Anwar (2021) investigated where consumers stand in terms of worldview.…”
Section: Previous Studiesmentioning
confidence: 99%